VIDEO EDUKASI UNTUK MEMINIMALISIR BULLYING VERBAL PADA TINGKAT REMAJA - Huda, Muhammad Miftahul Huda; Kahfi, Muhammad; Idris, Fathiyyah (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
Bullying cases at junior high school level have reached 50% based on data from FSGI. Meanwhile, another survey stated that the most cases of bullying were verbal bullying with a total of 87.6%. Based on this problem, the researcher chose this title, with the aim of finding a solution to reduce the rate of verbal bullying at the adolescent level. This research was conducted using observation and interview methods. With this, researchers found that a fairly effective way to minimize verbal bullying at the adolescent level is to provide educational videos.